1988
DOI: 10.1128/aem.54.12.3023-3033.1988
|View full text |Cite
|
Sign up to set email alerts
|

Survival of coliforms and bacterial pathogens within protozoa during chlorination

Abstract: The susceptibility of coliform bacteria and bacterial pathogens to free chlorine residuals was determined before and after incubation with amoebae and ciliate protozoa. Viability of bacteria was quantified to determine their resistance to free chlorine residuals when ingested by laboratory strains of Acanthamoeba castellanii and Tetrahymena pyriformis. Cocultures of bacteria and protozoa were incubated to facilitate ingestion of the bacteria and then were chlorinated, neutralized, and sonicated to release intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
0
2

Year Published

1989
1989
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(103 citation statements)
references
References 53 publications
1
100
0
2
Order By: Relevance
“…They are likely to constitute an important environmental reservoir for transmission of E. coli O157:H7 and other pathogens. Bacterial pathogens including Vibrio, Legionella, Mycobacteria, enteropathogenic E. coli, and the meningitis-causing E. coli strain K1 multiply and/or survive within protozoa (King et al, 1988;Werner et al, 1990;Barker & Brown, 1994;Fields, 1996;Steinert et al, 1998;Alsam et al, 2006;Huws et al, 2008). Escherichia coli O157 and non-O157 strains have been shown to survive within the environmental protozoa Acanthamoeba polyphaga and Acanthamoeba castellanii (King et al, 1988;Barker et al, 1999;Carruthers et al, 2010).…”
Section: Factors Involved In Environmental Persistence Of E Coli O15mentioning
confidence: 99%
See 1 more Smart Citation
“…They are likely to constitute an important environmental reservoir for transmission of E. coli O157:H7 and other pathogens. Bacterial pathogens including Vibrio, Legionella, Mycobacteria, enteropathogenic E. coli, and the meningitis-causing E. coli strain K1 multiply and/or survive within protozoa (King et al, 1988;Werner et al, 1990;Barker & Brown, 1994;Fields, 1996;Steinert et al, 1998;Alsam et al, 2006;Huws et al, 2008). Escherichia coli O157 and non-O157 strains have been shown to survive within the environmental protozoa Acanthamoeba polyphaga and Acanthamoeba castellanii (King et al, 1988;Barker et al, 1999;Carruthers et al, 2010).…”
Section: Factors Involved In Environmental Persistence Of E Coli O15mentioning
confidence: 99%
“…In addition to enhanced environmental survival, bacterial co-habitation with protozoa could induce adaptative changes in bacteria (King et al, 1988;Barker et al, 1993). Furthermore, we recently observed that the coculture of E. coli O157:H7 with A. castellanii increased bacterial persistence over 3 weeks (Chekabab et al, 2012).…”
Section: Factors Involved In Environmental Persistence Of E Coli O15mentioning
confidence: 99%
“…This compartment may constitute a rich source of nutrients for the bacteria and is probably recognized as a cellular compartment. King et al (1988) proposed that resistance to digestion by predatory protozoa was an evolutionary precursor of pathogenicity in bacteria and that today it is a mechanism for the survival of fastidious bacteria in dilute and inhospitable aquatic environments. L. pneumophila proliferates intracellularly in various species of protozoa, surviving at some temperatures and proliferating at others within vacuoles studded with ribosomes (Kikuhara et al, 1994).…”
Section: Protozoa and Pathology Of Legionellosismentioning
confidence: 99%
“…Baré et al, unpublished data). Although some data are available on Campylobacter-protozoan interactions (King et al, 1988;Axelsson-Olsson et al, 2005;Snelling et al, 2005), more information is needed about the effect of environmental factors and bacteria-specific characteristics on, and the nature of their association with protozoa.…”
Section: Introductionmentioning
confidence: 99%